Nutrition and Urological Disorders: From Nephrolithiasis to Uro oncology – Practical Implications for Everyday Practice - Kandefer, Tomasz; Sroka, Maria; Wasiniewska, Weronika; Barański, Marcin (Quality in Sport, 2026)
Nutrition has become a key determinant across urological disorders, with particularly strong evidence in nephrolithiasis and emerging data in urologic oncology and functional conditions. This narrative review synthesizes current evidence on the role of diet, obesity, and broader dietary patterns in nephrolithiasis and urologic cancers, and translates these findings into practical dietary counselling strategies for everyday clinical practice. A selective review of recent guidelines, systematic reviews, meta-analyses, and key observational and mechanistic studies was performed, focusing on dietary and lifestyle determinants of kidney stone disease and major urologic malignancies, with particular attention to clinically actionable recommendations. For nephrolithiasis, convergent guideline and meta-analytic data support high fluid intake, normal dietary calcium, reduced sodium and animal protein, and plant-rich dietary patterns (DASH- or Mediterranean-like) as first-line preventive strategies rather than optional adjuncts. In urologic oncology, obesity and adverse dietary patterns are consistently associated with increased risk of kidney and bladder cancers and aggressive prostate cancer, while greater adherence to plant-forward, cancer-prevention dietary guidelines appears protective, although high-quality interventional data on survival remain limited. Emerging evidence suggests that diet, body composition, and the gut microbiome may modulate response to systemic therapies, including immune checkpoint inhibitors, but this area is still in early translational development. Current evidence justifies routine, pattern-based dietary counselling—centered on adequate hydration, plant-forward eating, moderation of sodium and animal protein, and weight management—as a core component of nephrolithiasis prevention and urologic cancer risk reduction.